Evaluation of Streptocin SH3, a Bacteriocin produced by Streptococcus sanguinis isolated from Human Dental Plaque - Al-Taie, Shahad Fadhil; Al- Musawi, Muna T.; Rasheed, Zaid S. (AL-Kindy College Medical Journal, 2022)
Background: Bacteriocin is a peptidic toxin has many advantages to bacteria in their ecological niche and has strong antibacterial activity. Objective: The aim of this study was to evaluation of bacteriocin using Streptococcus sanguinis isolated from human dental caries. Subjects and Methods: Thirty five streptococcus isolates were diagnosed and tested for their production of bacteriocin, and then the optimal conditions for production of bacteriocin were determined.  After that, the purification of bacteriocin was made partially by ammonium sulfate at 95% saturation levels, followed by and gel filtration chromatography using Sephadex G-50 column. Finally, physical characteristics were also studied and determined the bacteriocin stability.Results: Among all streptococcal isolates, the S. sanguinis SH3 isolate with batter antimicrobial activity was selected, and used in further experiments. The optimum conditions for bacteriocin production were in Todd Hewitt broth (THB) supplemented with 1% glucose at 37°C for 24h under anaerobic conditions and inoculum size of (1.2 ˟ 109CFU/ml) and pH 7, where the inhibition zone diameter reached to 29 mm against Enterococcus faecalis. The purified bacteriocin had high inhibitory activity against S. pneumoniae, S. pyogenes, E. faecalis, E. faecium and  Leuconostoc mesenteroides. Streptocin SH3 keeps its effectiveness within the pH range 3-10, and temperature until 80ºC for 20 min.Conclusion: Bacteriocin produced from S. sanguinis has high activity against many pathogens and has high stability over wide ranges of temperature and pH, which makes it a good alternative in the medical and food preservation fields